Effect of Stratification on Biochemical Composition of Cedrus deodara - Sofi, Parvez Ahmad; Bhardwaj, S. D. (Indian Forester, 2007)
Cedrus deodara (Deodar) seeds collected from Lolab area of Kashmir valley after subjecting to different stratification durations were quantitatively examined for biochemical parameters. There was increase in the soluble protein and total sugar content of seeds upto 60 days of stratification and thereafter decreased while the starch content showed a continuous decline with the increase in stratification duration. Stratification of seed for 60 days resulted in an increase of 1.38 per cent soluble protein and 1.20 per cent total sugar than control.